Rainfall-Runoff Modelling in Tropical River Basin for Water Conservation Planning Using Water Recharge Ponds - M Yusfan Yuzanni; Chandra Setyawan; Sahid Susanto; Yekti Nugraheni (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Land conversion in river basins poses a threat to future water availability. This research aims to estimate water availability, particularly stream flow for planning of water conservation. Water availability was analyzed using a hydrology tank model. The model was calibrated by using stream flow data measured in a reservoir and then used to estimate water availability in the reservoir's catchment area. The value of model parameters such as wet infiltration coefficient (WIC), dry infiltration coefficient (DIC), soil moisture capacity (SMC), initial soil moisture (ISM), initial groundwater storage (IGWS), groundwater recession constant (k) was determined through the calibration process. The results showed that the model has good accuracy for stream flow calculation indicated by the value of statistical parameters i.e. coefficient of correlation (R) = 0.93, a volume of error (VE) = 0.04, and a coefficient of efficiency (CE) = 1.00. During the wet season, the specific maximum discharge is 0.11 m3s–1km–2. Meanwhile, the minimum specific discharge is 0.030 m3s–1km–2. These differences indicate that optimizing rainwater harvesting during the wet season is required. Rainfall-runoff modeling reveals the potential for surface runoff during the wet season is 1,139 mm. This finding provides an essential reference for water conservation, especially using water recharge ponds. Keywords: Hydrology tank model, Stream flow, Tropical river basin, Water availability, Water conservation.